ARE PSYCHIATRIC SYMPTOMS A CORE PHENOTYPE OF MYOCLONUS DYSTONIA SYNDROME CAUSED BY SGCE MUTATIONS?. Issue 9 (6th August 2013) - Peall, KJ; Smith, DJ; Kurian, MA; Wardle, M; Waite, AJ; Hedderly, T; Lin, JP; Smith, M; Whone, A; Pall, H; White, C; Lux, A; et al.
Abstract : Objective: Myoclonus Dystonia Syndrome (MDS) is a childhood onset, alcohol responsive movement disorder caused by mutations in the SGCE gene in a proportion of cases. Single family and case series have suggested co-morbid psychiatric disease but have not compared cases to a control group. Aims: To establish a cohort of MDS patients with SGCE mutations and a control group of alcohol-responsive tremor patients, and to systematically assess for psychiatric symptoms using standardised questionnaires. Method: We collected 27 patients with SGCE mutations and 45 tremor control cases. The MINI International Neuropsychiatric Interview, PHQ-9, MADRS, YBOCS and AUDIT were used to assess psychiatric disease according to DSM-IV criteria. Results: There was a higher rate of psychiatric disease in MDS patients compared to controls (p<0.05), specifically social phobia (p><0.05) and Obsessive-Compulsive disease (OCD) (p><0.001). Excess alcohol use was higher amongst the MDS group once cases ><18yrs were excluded. > Conclusion: Overall psychiatric disease is elevated amongst the MDS cohort compared to a control group with a chronic, socially stigmatizing disorder. OCD appears to be the greatest contributor to this effect and may reflect a pleiotropic function for the SGCE gene.